Problems and challenges of implementing interactive resources in educational institutions - Li, Ting; Koodoevna, Sartbekova Nurzhan; Li, Dehao; Li, Yixiu (Edelweiss Applied Science and Technology, 2025)
Educational institutions that deploy interactive resources such as virtual laboratories and augmented reality (AR) tools generally face three major challenges: difficulty in technology integration, gaps in teachers’ digital literacy, and imbalanced student participation. To address these issues, this study proposes a layered collaborative implementation framework. The lightweight technology layer, which includes a modular API (Application Programming Interface), decouples heterogeneous systems; the teacher empowerment layer offers personalized training based on cognitive diagnosis embedded in sandbox exercises; and the intelligent adaptation layer utilizes a multi-dimensional matrix to match resources and teaching scenarios in real time. The framework presented in this paper overcomes the separation of technology, people, and scenarios through a three-layer dynamic coupling mechanism. Pilot results indicate that the resource deployment cycle is reduced by approximately 56.8%, the teachers’ operational accuracy rate improves to 84.5%, classroom interaction frequency increases by 133.2%, and the proportion of highly engaged students reaches 67.4%. These findings demonstrate that the layered collaborative implementation framework provides a methodological approach for systematically solving implementation challenges through a collaborative integration mechanism.